2014
DOI: 10.1007/s10964-014-0152-5
|View full text |Cite
|
Sign up to set email alerts
|

Divergence Between Adolescent and Parental Perceptions of Conflict in Relationship to Adolescent Empathy Development

Abstract: Adolescents' developing empathy may be associated with the frequency of conflict with parents, as well as the level of agreement between adolescent and parental perceptions of the frequency of such conflicts. This 6-year longitudinal study investigated the link between adolescent empathy development and perceptions of the frequency of parent-child conflict, as reported by 467 adolescents (43% female, from age 13) and both parents. First, we investigated heterogeneity in empathy development by identifying class… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 54 publications
4
54
0
2
Order By: Relevance
“…Moreover, few studies in this field have been longitudinal. A study that used the same methodology as this study only found temporary changes in parent–adolescent divergent views of conflict (Van Lissa et al., ). Therefore, this study adds to this body of research, using a longer time frame spanning adolescence, as well as a combination of methods to detect divergence (latent means comparisons and change in correlations with age).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, few studies in this field have been longitudinal. A study that used the same methodology as this study only found temporary changes in parent–adolescent divergent views of conflict (Van Lissa et al., ). Therefore, this study adds to this body of research, using a longer time frame spanning adolescence, as well as a combination of methods to detect divergence (latent means comparisons and change in correlations with age).…”
Section: Discussionmentioning
confidence: 93%
“…To investigate reporter differences, we then computed a series of Wald tests to test for differences in means of the intercepts and slopes among the dyads (adolescent vs. father, adolescent vs. mother, father vs. mother), a technique that has been applied by Van Lissa et al. (). Again, a multiple group approach was used to test for gender differences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings therefore indicate that parents with more empathic brain responses to their child's error, as evidenced by vmPFC activation, also engage in more positive parenting behaviors in daily life as reported by their child. Much of the past research on empathy and parenting has been related to the child's development of empathy rather than parental empathy (e.g., Yoo et al, 2013;Van Lissa et al, 2015). The current study adds to this literature by highlighting the importance of parental empathy and its underlying neurobiology for positive parenting behaviors, which likely impact adolescent mental health (Tabak and Zawadzka, 2017).…”
Section: Discussionmentioning
confidence: 82%
“…For instance, what does happen when personal and others' ratings of an adolescent's morality, competence, and sociability are highly divergent (e.g., an individual's perception of his/her own high level of morality is not confirmed by another person)? This is an important future direction of research, as divergence in perceptions may be due to various factors, such as differences in empathy (Van Lissa et al 2014) and can have important psychosocial consequences (e.g., decreasing adjustment; Zimmer-Gembeck et al 2007). Thus, it is worth investigating how divergence in rating these dimensions influences interpersonal and intergroup interactions.…”
Section: Strengths Limitations and Suggestions For Future Researchmentioning
confidence: 99%